TOWARDS ACHIEVING UNIVERSAL EARLY CHILDHOOD EDUCATION IN THE REPUBLIC OF UZBEKISTAN - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Some of UNICEF’s efforts to improve preschool education in Uzbekistan are outlined in this article. And a report on the status is given. Information is provided on how to improve preschool education and achievements.